Opposition coalitions in the Middle East: Origins, demise, and afterlife?. Issue 4 (8th August 2019) - Durac, Vincent
ABSTRACT: Oppositional coalitions, networks and social movements in the MENA region have long attracted scholarly attention. The Arab uprisings of 2011 have given renewed strength to this focus. In the literature that has followed, a great deal of attention has been devoted to cross-ideological coalitions, their origins and their trajectories. This literature has also tended to focus on a strict dichotomy between success and failure. The collection of papers in this Special Issue moves away from some of these narrower approaches to coalitions and, in doing so, expands significantly on how we understand coalition building in the MENA region. This Afterword examines the key questions raised by these papers regarding why, how and when coalitions are formed, how those who are challenged by the emergence of new coalitions respond, and how this impacts on those coalitions. Finally, it examines the related questions of how internal divisions from within, and challenge from without, weaken coalitions and lead to their demise as well as the longer term and potentially 'transformative' impact of the act of coalition building in particular settings.